COOPERATIVE INTEGRATED READING AND COMPOSITION BASED ON SCIENTIFIC APPROACH TO IMPROVE WRITING ACHIEVEMENT - Ariyani, Farida; Sutarsyah, Cucu; Sukirlan, Muhammad (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2024)
Writing is a crucial aspect of individuals' lives, especially for students, as it involves both the process and product of language. This study explores the challenges students face in writing, including the impact of teaching methods and the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) method based on the Scientific Approach (CIRSA) in enhancing students' writing skills. This study employs quasi-experimental pretest-posttest design to investigating the significant difference both of methods with 30 samples in the experiment class and 30 samples in the control class. Through the independent sample t-test hypotheses are formulated and tested (Î± values are 0.05), providing a structured framework to draw meaningful inferences about the populations studied. The empirical findings of this study aimed to discern significant differences in writing achievement between the CIRSA and CIRC models (sig. 0.002 0.05). Aligned with educational theories, the N-gain score was utilized to evaluate students' progress during the learning process. So, The CIRSA Model (N-Gain 41%) is more effective than CIRC (N-Gain 32%). Then, this study explored the significant correlation between students' perceptions of the CIRSA model and their writing achievement (t-value of 6.268 1.701).